Peningkatan Pengetahuan Sistem Pemasaran E-Commerce pada Produk Olahan Udang di Usaha Mikro Kecil Menengah Desa Sungsang - Riani, Ira Gusti; Yulia Hapsari; Aldilla Sari Utami; Nia Boru Ritonga; Madyasta Anggana Rarassari; Raudhatus Saadah; Eka Nurriza Khairunnisa (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
Sungsang Village, Banyuasin Regency, South Sumatra, is one of Indonesia’s leading shrimp-producing areas, with an annual production potential of 2,536.40 tons. This potential has encouraged the development of community-based businesses producing value-added products such as shrimp stock powder and shredded shrimp heads. However, limited knowledge of e-commerce and digital marketing has restricted market expansion. This community service program aimed to improve participants’ knowledge and skills in implementing e-commerce-based marketing through website development and digital promotion. The program consisted of training, practical workshops, and mentoring on website management and online marketing strategies delivered by competent facilitators. Program effectiveness was evaluated using pre-test and post-test assessments supported by SWOT analysis. The results demonstrated improved participant understanding of e-commerce-based marketing, while the SWOT analysis identified stronger marketing capabilities and broader business opportunities. These findings indicate that integrating digital marketing education with website-based mentoring can enhance the competitiveness, marketing effectiveness, and business sustainability of community-based seafood processing enterprises.